2021
DOI: 10.1186/s12885-021-08343-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic comorbidities and the association with risks of recurrent metastatic disease in breast cancer survivors

Abstract: Background Obesity and other metabolic comorbidities affect over 10% of patients with breast cancer and are closely related with adverse outcomes. Although metabolic comorbidities among breast cancer patients in low- and middle-income countries are suggested to be lower, only a few studies are currently available. Effective management of metabolic comorbidities in cancer patients has been associated with better outcomes. Methods Non-metastatic brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Breast cancer incidence is continuously increasing over the past decades causing a significant morbidity and economic burden including in countries with traditionally low incidence rates (Sung et al, 2021). More than 90% of cancer-associated mortality is associated with primary distant metastases (Anwar et al, 2021;Harries et al, 2014). At primary diagnosis of breast cancer, around 5% patients presented with bone metastases (Harries et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer incidence is continuously increasing over the past decades causing a significant morbidity and economic burden including in countries with traditionally low incidence rates (Sung et al, 2021). More than 90% of cancer-associated mortality is associated with primary distant metastases (Anwar et al, 2021;Harries et al, 2014). At primary diagnosis of breast cancer, around 5% patients presented with bone metastases (Harries et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The meta‐analyses included 101 publications reporting postdiagnosis BMI (assessed from at‐diagnosis to on average 5.8 years postdiagnosis), waist circumference (at‐diagnosis to 7.9 years postdiagnosis), waist‐to‐hip ratio (at‐diagnosis to 2.5 years postdiagnosis) and pre‐ to postdiagnosis weight gain or loss (from 1 year before to 1 year or more after diagnosis) 27,39‐138 . In addition, 119 publications were descriptively synthesized…”
Section: Resultsmentioning
confidence: 99%
“…This risk was even greater if the comorbidity was diagnosed within 5 years of cancer diagnosis, as opposed to more than 5 years since diagnosis [ 57 ]. A similar study in Shanghai found that diabetes and history of stroke were associated with an increased risk of all-cause and non-breast cancer mortality, respectively [ 58 ].…”
Section: Discussionmentioning
confidence: 99%